Multicentre clinicopathological study of adenoid cystic carcinoma: A report of 296 cases. (15th January 2021) - Huang, Zheng; Pan, Juan; Chen, Jiaorong; Wu, Shidi; Wu, Ting; Ye, Haihua; Zhang, Hongfeng; Nie, Xiu; Huang, Changzheng
Abstract: Aims: Adenoid cystic carcinoma (ACC) is a distinctive tumour. Limited studies involving a large population have reported multicentre systematic analyses of the clinical, pathological and immunohistochemical (IHC) features of ACC as well as the potential role of IHC markers in the prognosis of ACC. Methods and Results: The clinical, histopathological and IHC data of 296 cases obtained from two tertiary hospitals were analysed. The age at onset ranged from 12 to 87 years with a median age of 52 years. The male‐to‐female ratio was 1:1.3. Patients with ACC arising from the lacrimal gland were younger than those with tumours arising from other sites. Patients with tumours in the extra auditory canal and nasopharynx were older than those with tumours in other locations. Histopathologically, solid type ACC was the most frequent in the nasal cavity and paranasal sinus (6/51) group. Tumours arising from the oral cavity most commonly showed perineural invasion (10/60) and margin positivity (11/60). IHC analyses showed that CK8/18, CK7, CK14, epithelial membrane antigen and CD117 were expressed in 35/35 (100%), 87/88 (98.8%), 26/27 (96.2%), 42/43 (97.6%) and 113/120 (94.1%) patients, respectively. CK5/6, P63, smooth muscle actin, calponin and S100 were positively expressed in 73/73 (100%), 111/124 (89.5%), 38/43 (88.3%), 41/50 (82.0%) and 61/92 (66.3%) cases, respectively. S100 proteins were expressed in 54 (54/77) primary cases and two (2/9) metastatic cases ( p  = 0.013). Conclusions: ACC is a distinctive tumour that mainly affects middle‐aged and elderly individuals, with a mild female predominance. Loss of expression of S100 proteins may be a poor prognostic factor associated with metastasis. Abstract : Mean age (standard deviation) in each group. Patients with adenoid cystic carcinoma arising from the lacrimal gland showed the lowest median age (39 years, mean = 41.85 years). The highest median age (60.5 years, mean = 59.7 years) was observed in the nasopharynx group.